1999
DOI: 10.1901/jaba.1999.32-339
|View full text |Cite
|
Sign up to set email alerts
|

Using High‐probability Instruction Sequences With Fading to Increase Student Compliance During Transitions

Abstract: Making efficient transitions from one instructional activity to another has been shown to increase academic learning time and therefore student achievement. Because compliance with teacher instructions is a prerequisite for efficient transitions, we sought to determine if high-probability (high-p) instruction sequences issued by a classroom teacher would increase student compliance and decrease latency to comply during transitions. Three children in a regular second-grade classroom participated. Each day at th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
47
0
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(50 citation statements)
references
References 22 publications
2
47
0
1
Order By: Relevance
“…A closer examination of the data showed that increases in the percentage of engagement occurred during the first 3 min following the delivery of the high-p request sequence. Future research could evaluate methods to increase engagement time by enhancing the reinforcer quality during the high-p instructional sequence (Mace, Mauro, Boyajian, & Eckert, 1997) or by varying high-p requests (Ardoin, Martens, & Wolfe, 1999).…”
Section: Resultsmentioning
confidence: 99%
“…A closer examination of the data showed that increases in the percentage of engagement occurred during the first 3 min following the delivery of the high-p request sequence. Future research could evaluate methods to increase engagement time by enhancing the reinforcer quality during the high-p instructional sequence (Mace, Mauro, Boyajian, & Eckert, 1997) or by varying high-p requests (Ardoin, Martens, & Wolfe, 1999).…”
Section: Resultsmentioning
confidence: 99%
“…For instance, Ardoin, Martens, and Wolfe (1999) showed that second graders' difficult transition to a new activity was improved when their teacher delivered a series of five simple instructions just prior to the transition request. This approach likewise has been used to increase the rate of student academic responding.…”
Section: Examplesmentioning
confidence: 99%
“…The application of an intervention based on the momentum analogy can provide practitioners with a set of procedures to apply in situations where a behavior with a low-probability of occurrence needs to be increased. Ardoin, Martens, and Wolfe (1999), for example, found that a series of high-p requests reduced transition time from one instructional activity to another for a group of typical children in a general education setting. Similarly, Wehby and Hollahan (2000) found that high-p request sequences increased compliance to begin math tasks for a student with a learning disability.…”
mentioning
confidence: 99%